SISTEM INFORMASI PENGELOLAAN SERTIFIKAT TANAH PADA BADAN PERTANAHAN NASIONAL JAKARTA - Priyono, Agil Hendro; -, Amrin (Jurnal Mantik Penusa, 2019)
Nowadays the internet is needed in all fields as a source of information and telecommunications that is fast and efficient. The use of the internet has become an important requirement for the whole community. Likewise, service at the Jakarta National Land Agency (BPN) office as a means to take care of all matters relating to land. This creates difficulties for people who are far from the BPN office environment to obtain the required information. Therefore, we need an information media website that contains various information services related to land that can be accessed by all levels of society. In this study, the authors designed a web-based land certificate management information system. The method used for software development is the waterfall method. The results of this study are websites that provide information services relating to land certificates, land sales, land ownership. This website is expected to assist the Jakarta BPN office in providing information services to the public and facilitate the BPN service process. Keywords: information systems,lLand certificates, web, UML, waterfall method